2011
DOI: 10.1159/000331711
|View full text |Cite
|
Sign up to set email alerts
|

The Antiapoptotic Effect of Granulocyte Colony-stimulating Factor Reduces Infarct Size and Prevents Heart Failure Development in Rats

Abstract: Background/Aim. Granulocyte colony-stimulating factor (G-CSF) reduces myocardial injury and improves cardiac function after myocardial infarction (MI). We investigated the early alterations provided by G-CSF and the chronic repercussions in infarcted rats. Methods. Male Wistar rats (200-250g) received vehicle (MI) or G-CSF (MI-GCSF) (50 µg/kg, sc) at 7, 3 and 1 days before MI surgery. Afterwards MI was produced and infarct size was measured 1 and 15 days after surgery. Expression of anti- and proapoptotic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…However, a different regulation pattern is noticed during the development of heart failure. The GCSF reduces myocardial injury and improves cardiac function in rats with acute and chronic myocardial infarction [31,32] and is regarded as a potential cardiac repair therapy for subjects with myocardial infarction [30]. The GMCSF is able to enhance collateral blood flow of patients with chronic myocardial infarction [33]; however, plasma levels of GMCSF in patients with heart failure are highly associated with LV dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, a different regulation pattern is noticed during the development of heart failure. The GCSF reduces myocardial injury and improves cardiac function in rats with acute and chronic myocardial infarction [31,32] and is regarded as a potential cardiac repair therapy for subjects with myocardial infarction [30]. The GMCSF is able to enhance collateral blood flow of patients with chronic myocardial infarction [33]; however, plasma levels of GMCSF in patients with heart failure are highly associated with LV dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is also used to prevent or shorten neutropenia in chemotherapy-induced or primary congenital neutropenia [42], and mobilize hematopoietic stem cells to peripheral blood for transplantation [43]. Probably because of the anti-apoptotic and anti-inflammatory effects, G-CSF has also been used to treat nonhematopoietic targets including cerebral ischemia [44], spinal cord ischemia [45], infarct heart [46], and end stage liver disease [47]. Consequently, the effects of G-CSF on other cell types (e.g., macrophage, lymphocyte, endothelial, dendritic cells, cardiomyocytes, and smooth muscle) may not be completely excluded from the rescue mechanism of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF also induced antiapoptotic proteins and inhibited apoptotic death of cardiomyocytes [14]. Baldo MP et al recently reported that G-CSF preserved left ventricular function through early infarct size reduction and the attenuation of cardiac remodeling after MI via anti-apoptotic protein upregulation and an early reduction in cardiomyocyte apoptosis [15]. Minatoguchi et al hypothesized that G-CSF accelerate the healing of MI wounds and they reported that it accelerated absorption of necrotic tissues by increasing macrophage numbers, and reduced granulation and scar tissue by promoting the expression of matrix metalloproteinases [16].…”
Section: Discussionmentioning
confidence: 99%